Impact of perioperative use of GnRH agonist or dienogest on ovarian reserve after cystectomy for endometriomas: a randomized controlled trial - Ayako Muraoka; Satoko Osuka; Atsushi Yabuki; Bayasula; Masato Yoshihara; Hideaki Tanaka; Reina Sonehara; Natsuki Miyake; Mayuko Murakami; Sayako Yoshita; Natsuki Nakanishi; Tomoko Nakamura; et al. (Reproductive Biology and Endocrinology, 2021)
Abstract Background Ovarian endometrioma is a common gynecological disease that is often treated with surgery or hormonal treatment. Ovarian cystectomy, a surgical procedure for ovarian endometrioma, can result in impaired ovarian reserve. Methods We conducted a randomized controlled trial to evaluate the efficacy of hormonal treatment [gonadotropin-releasing hormone agonist (GnRHa) or dienogest (DNG)] for preserving ovarian reserve after cystectomy for ovarian endometrioma. The primary endpoint was the level of serum Anti-Müllerian hormone (AMH) as a marker of ovarian reserve. Results Before and after laparoscopic surgery, 22 patients in the GnRHa group and 27 patients in the DNG group were administered hormonal treatment for a total of 4 months. After 1-year follow-up, >60% of the patients in the DNG group retained over 70% of their pretreatment AMH levels, whereas no patient in the GnRHa group retained their AMH levels after cystectomy (P < 0.01). Interleukin-6 (IL-6) is a key cytokine involved in inflammation. Compared with the GnRHa group, patients in the DNG group had lower IL-6 levels at the end of treatment. Conclusions Our data revealed that DNG is more effective than GnRHa in preserving ovarian reserve after cystectomy of ovarian endometrioma. This is achieved through the reduction of the inflammatory response during the perioperative period and other endometriosis-related inflammatory reactions. Trial registration The registration number of this trial is UMIN-CTR, UMIN000018569, registered 6 August 2015, https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000021492 , and Japan Registry of Clinical Trials, jRCTs041180140, registered 29 March 2019, https://jrct.niph.go.jp/en-latest-detail/jRCTs041180140 . This randomized controlled trial was conducted in accordance with the CONSORT guidelines.